PENGARUH PENDIDIKAN SEKS TERHADAP MENINGKATNYA PERILAKU SEKS BEBAS DI KALANGAN REMAJA DI KOTA KUPANG - Harun Y. Natonis; Febrinia S. Malaikari; Andiani Bolla; Dewi R. Bani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Sex education is an important part of efforts to shape healthy and responsible sexual behavior among adolescents. However, in various regions, including the city of Kupang itself, sexuality education is often perceived ambiguously and even accused of contributing to an increase in promiscuous behavior among adolescents. This study aims to examine in depth the relationship or connection between sexuality education and promiscuous behavior among adolescents in the city of Kupang by examining the concept, implementation, and socio-cultural context surrounding it. This study was conducted using a qualitative approach, with literature review and thematic analysis methods on various relevant previous studies in terms of Christian theological education and social health. The results of the study show that sexuality education that is delivered partially, solely biologically, and not based on moral values and local culture, has the potential to be misunderstood by today's youth, thereby continuing to encourage risky sexual behavior. Conversely, comprehensive contextual sexuality education that involves families, schools, and all elements of society, including religious leaders, has been proven to play a more preventive role in reducing promiscuous sexual behavior among adolescents. Therefore, strengthening a holistic sexuality education model has become a fundamental need, even an urgent need, in Kupang City, East Nusa Tenggara.